The Role of Social Service Activities in the Social Intelligence of Students at Al-Muhajirin 2 Boarding School - Bilqis Kusuma Wardani; Chusnul Chotimah; Hidayatur Rohmah (Kuttab: Jurnal Ilmu Pendidikan Islam, 2026)
This study addresses the need to understand how social service activities function as a form of social education in Islamic boarding schools. It aims to describe the implementation of social service programs, identify supporting and inhibiting factors, and explore their perceived impact on students at Al-Muhajirin 2 Islamic Boarding School in Tambakberas, Jombang. This research employs a qualitative descriptive approach. The findings show that students' involvement in religious and community-based programs, such as congregational worship, Qur'an recitation, khotmil Qur'an, rotibul haddad, religious lectures, teaching at TPQ, community visits, and organizing public gatherings, contributes to the development of social awareness and interaction skills. These activities support the formation of responsibility, independence, environmental sensitivity, self-confidence, communication and collaboration skills, openness to diversity, and social adaptability. The study concludes that social service activities are an important part of social education within the boarding school environment.